2020
DOI: 10.22219/celtic.v7i2.12766
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Health Minister in Handling Covid-19 in Indonesia: A Critical Discourse Analysis

Abstract: COVID-19 outbreaks that threaten human health have become a pandemic. As the Health Minister in Indonesia, the actions were taken by the Letjen TNI (Purn) Dr. dr. Terawan Agus Putranto, Sp. Rad. (K) in handling this pandemic is in the spotlight. There are so many media that providenews related to the efforts of the Health Minister in handling this case, one of which is The Jakarta Post. This study aims to describe the representation of Mr. Terawan as Health Minister in handling COVID-19 cases in Indonesia in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The other nomination strategy used by The Connexion France is the proper name "Macron". Anggraeni & Amalia (2020) Synecdoche was also used as a nomination strategy to indicate that Emmanuel Macron is someone who represents France. Kurniawan & Utami (2017) found that synecdoche draws attention to the social actor's position as the President and shows his every action represents the action that the government and country take.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other nomination strategy used by The Connexion France is the proper name "Macron". Anggraeni & Amalia (2020) Synecdoche was also used as a nomination strategy to indicate that Emmanuel Macron is someone who represents France. Kurniawan & Utami (2017) found that synecdoche draws attention to the social actor's position as the President and shows his every action represents the action that the government and country take.…”
Section: Discussionmentioning
confidence: 99%
“…Baykal (2009) analysed the discourse of the 2005 gentrification process in Turkey found one discursive strategy, while Hussein & Ahmed (2020) found three discursive strategies to reveal how foreign policy goals, identities, and ideologies are communicated in EU discourse. Three studies took place in Indonesia; Purwanto (2017) found all five discursive strategies to analyse the Facebook posts of a major city mayor, Anggraeni & Amalia (2020) found two discursive strategies to see the representation of Indonesia's Minister of Health regarding his conduct to address the Covid-19 pandemic, and Kurniawan & Utami (2017) found two strategies to see how Indonesia's news represent the Indonesian President, Joko Widodo.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, the author sidesteps monotonous repetition while establishing Mr. Terawan's centrality and detailing his professional activities. Its performance as health minister during the COVID-19 outbreak could have been better (Anggraeni & Amalia, 2020). Even though illocutionary acts and critical discourse analysis (CDA) have been the subject of significant study, researchers still need to comprehensively examine illocutionary acts within internet news discourses concerning election postponement.…”
Section: Introductionmentioning
confidence: 99%